Hippocampal firing fields anchored to a moving object predict homing direction during path-integration-based behavior - Najafian Jazi, Maryam; Tymorek, Adrian; Yen, Ting-Yun; Jose Kavarayil, Felix; Stingl, Moritz; Chau, Sherman Richard; Baskurt, Benay; García Vilela, Celia; Allen, Kevin (Nature Communications, 2023)
Homing based on path integration (H-PI) is a form of navigation in which an animal uses self-motion cues to keep track of its position and return to a starting point. Despite evidence for a role of the hippocampus in homing behavior, the hippocampal spatial representations associated with H-PI are largely unknown. Here we developed a homing task (AutoPI task) that required a mouse to find a randomly placed lever on an arena before returning to its home base. Recordings from the CA1 area in male mice showed that hippocampal neurons remap between random foraging and AutoPI task, between trials in light and dark conditions, and between search and homing behavior. During the AutoPI task, approximately 25% of the firing fields were anchored to the lever position. The activity of 24% of the cells with a lever-anchored field predicted the homing direction of the animal on each trial. Our results demonstrate that the activity of hippocampal neurons with object-anchored firing fields predicts homing behavior.